2023
DOI: 10.1002/anie.202306020
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization and Cyclization Mechanism of a Diterpene Synthase Catalyzing the Skeleton Formation of Cephalotane‐Type Diterpenoids

Abstract: CsCTS, a new diterpene synthase from Cephalotaxus sinensis responsible for forming cephalotene, the core skeleton of cephalotane‐type diterpenoids with a highly rigid 6/6/5/7 tetracyclic ring system, was functionally characterized. The stepwise cyclization mechanism is proposed mainly based on structural investigation of its derailment products, and further demonstrated through isotopic labeling experiments and density functional theory calculations. Homology modeling and molecular dynamics simulation combined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…CharTPS7 from C. harringtonia and ChaiTPS7 from C. hainanensis by Wang and co-workers, 27 and CsCTS from C. sinensis by Dai and co-workers. 28 The discovered diTPSs catalyze the direct cyclization of GGPP into a distinctive cephalot-12-ene skeleton, which, although different from the previously hypothesized cephalot-3-ene, was believed to be a more plausible precursor. The biosynthetic mechanism for the formation of the 7,6,5,6-fused tetracyclic scaffold (Scheme 4) was proposed based on isotopic labelling experiments, quantum chemical calculations, and structural analyses of the derailment intermediates.…”
Section: Biosynthesis Of Cephalotane Diterpenoidsmentioning
confidence: 98%
See 2 more Smart Citations
“…CharTPS7 from C. harringtonia and ChaiTPS7 from C. hainanensis by Wang and co-workers, 27 and CsCTS from C. sinensis by Dai and co-workers. 28 The discovered diTPSs catalyze the direct cyclization of GGPP into a distinctive cephalot-12-ene skeleton, which, although different from the previously hypothesized cephalot-3-ene, was believed to be a more plausible precursor. The biosynthetic mechanism for the formation of the 7,6,5,6-fused tetracyclic scaffold (Scheme 4) was proposed based on isotopic labelling experiments, quantum chemical calculations, and structural analyses of the derailment intermediates.…”
Section: Biosynthesis Of Cephalotane Diterpenoidsmentioning
confidence: 98%
“…Similarly, Dai's group revealed the critical residues, F613 and W756, for the functionality and catalytic roles of CsCTS. 28 They also found that V610F variant of taxadiene synthase TbTS could not generate taxadiene, only yielding cephalotene, albeit in a very small quantity. These findings offer insight into the possibility that closely related cephalotene and taxadiene synthase may have experienced divergent evolution, resulting in different biosynthetic pathways for two species-specific diterpene frameworks.…”
Section: Biosynthesis Of Cephalotane Diterpenoidsmentioning
confidence: 98%
See 1 more Smart Citation
“…Considering the inclusion of diverse characteristics in PdiTPSs, we hypothesize that these two motifs may represent the characteristic site atlas of residues around the substrates of PdiTPSs. Then, pyScoMotif [59] has been used to search for similar 3D structural motifs of these two motifs in newly characterized PdiTPSs and unreviewed terpene synthases, and the results indicate that these motifs are even present in PdiTPSs that produce new terpene scaffolds [82]. Furthermore, these two motifs can rectify incorrectly annotated terpene synthases obtained from UniProt.…”
Section: The Spatial Landscape Of Conserved Residues and Less Conserv...mentioning
confidence: 99%
“…A new diterpene synthase, CsCTS from Cephalotaxus sinensis , responsible for the assembly of the C20 skeleton of the cephalotane-type diterpenoid, cephalotene 22 has been characterised. 21 Feeding studies, as well as molecular docking and simulation experiments has generated insight into the unusual, stepwise cyclisation mechanism of CsCTS, which involves a carbocation cascade process. Four new tetronate natural products, including konjuemycin C2 23 have been isolated from the coral-associated actinomycete, Pseudonocardia kongjuensis SCSIO 11457.…”
mentioning
confidence: 99%